2011
DOI: 10.1089/scd.2009.0490
|View full text |Cite
|
Sign up to set email alerts
|

Betacellulin Overexpression in Mesenchymal Stem Cells Induces Insulin Secretion In Vitro and Ameliorates Streptozotocin-Induced Hyperglycemia in Rats

Abstract: Betacellulin (BTC), a ligand of the epidermal growth factor receptor, has been shown to promote growth and differentiation of pancreatic b-cells and to improve glucose metabolism in experimental diabetic rodent models. Mesenchymal stem cells (MSCs) have been already proved to be multipotent. Recent work has attributed to rat and human MSCs the potential to differentiate into insulin-secreting cells. Our goal was to transfect rat MSCs with a plasmid containing BTC cDNA to guide MSC differentiation into insulin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Once a person is diagnosed with DM, he will generally need to take drugs or insulin all his life, which can cause a great deal of disruption to his work and life in general. Allogeneic islet transplantation serves as a source of insulin-secreting beta- , Xuefeng Zhang 1) , Meirong Zhang 1) , Hong Gao Abstract. Previous studies have shown that several types of stem cells can differentiate into insulin-secreting islet betacells and that these cells can reduce blood glucose in some trials, but there has been no report of a long-term follow-up.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Once a person is diagnosed with DM, he will generally need to take drugs or insulin all his life, which can cause a great deal of disruption to his work and life in general. Allogeneic islet transplantation serves as a source of insulin-secreting beta- , Xuefeng Zhang 1) , Meirong Zhang 1) , Hong Gao Abstract. Previous studies have shown that several types of stem cells can differentiate into insulin-secreting islet betacells and that these cells can reduce blood glucose in some trials, but there has been no report of a long-term follow-up.…”
mentioning
confidence: 99%
“…However, limited availability of islets, high rates of islet graft failure, and the need for life-long non-specific immunosuppressive therapy are major obstacles to the widespread application of this therapeutic approach. Previous studies have shown that several types of stem cells can differentiate into islet insulin-secreting beta-cells [1][2][3] and that these cells can reduce blood glucose levels in animal models. Thus the outcome of such stem cell studies has established the foundation for overcoming DM.…”
mentioning
confidence: 99%
“…Betacellulin, a ligand of epidermal growth factor receptor, is expressed abundantly in the pancreas and intestine. Paz et al (2011) overexpressed betacellulin in rat bone-marrow-derived MSCs and reported the formation of IPCs. Stable expression of Pdx-1 in adipose tissue-derived MSC did not induce a pancreatic phenotype in vitro, but these cells were able to differentiate into IPCs and reduce hyperglycemia in streptozotocin-treated diabetic mice (Kajiyama, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The most promising way to achieve islet neogenesis, is therapeutically inducing endogenous stem or progenitor cells to develop into islets (Guo and Hebrok 2009). The islet progenitor cells could be obtained from different sources, including pancreatic islets (Smukler et al 2011), pancreatic ductal tissue (Lin et al 2006), brain derived pluripotential cells (Saljooque et al 2011), bone marrow and umbilical cord blood (Gao et al 2008;Paz et al 2011), and so on. However, hES and pluripotent stem cells are easy to induce but have a high tumorgenicity.…”
Section: Establishment Of Pancreatic B Cell Proliferation Modelmentioning
confidence: 99%